Influence of Reaction Parameters on Nanogold-Catalyzed Glucose and Xylose Oxidation : A Joint Experimental and DFT Study - Oña, Jay Pee (American Chemical Society, 2025)
The electrocatalytic oxidation (ECO) of glucose on gold requires alkaline conditions and relatively high potentials (>0.3 V-RHE). Although the adsorption of hydroxide ions (OHads) is also known to occur under these conditions, the generally accepted proton-coupled electron transfer mechanism for sugar ECO does not explicitly state the role of OHads in the sugar adsorption or oxidation steps. To investigate this, we carried out a combined experimental and density functional theory (DFT) study on the ECO of glucose and xylose over a nanogold catalyst under temperature and pH control. Grand canonical DFT (GC-DFT) was used to identify the preferred reaction mechanism in which OHads facilitates the thermodynamically feasible formation of gluconic and xylonic acid. Calculated results also showed that OHads plays a role in improving the acid selectivity. Constant-potential electrolyses in sugar solutions were performed using mesoporous (Sibunit) carbon-supported Au nanoparticles (AuNPs) with an average cluster size of 4.7 nm. Experimental results showed that the highest conversions for glucose (57.7\%) and xylose (49.4\%) were obtained at 25 degrees C and pH 12.5, with gluconic and xylonic acid selectivity of 81.5 and 87.8\%, respectively. The catalytic activities were high considering the low Au loading (similar to 0.1\% wt). Higher pH led to a decrease in the ECO rate possibly due to excess hydroxide ions blocking active sites for sugar adsorption. Our results highlight the importance of computational studies in elucidating reaction mechanisms for sugar ECO where sugar acids are the main oxidation products. This is crucial in designing reaction systems for the viable production of these value-added chemicals from biomass.